Effect of N-Acetylcysteine on IL-10 and Total Lymphocyte Count in HIV Infected Patients Undergoing Antiretroviral Treatment (Journal of Medicine, 2021)
Objective: To determine NAC oral administration’s effect on changes in IL-10 levels and total lymphocyte count (TLC) in patients with HIV/AIDS in Dr Mohammad Hoesin Hospital, Palembang.Material and Methods: This study was a double-blind, randomized clinical trial. A total of 32 HIV/AIDS patients undergoing ARV treatment were randomly divided into two groups: the placebo and NAC groups. In the placebo group, patients were given capsules containing lactose at a dose of 3x1 capsules/ day, while the NAC group, were given NAC at a dose of 3x200 mg/day. Each group was treated for 12 weeks.Results: NAC administration significantly reduced IL-10 levels P= 0.038 but could not significantly increase TLC after treatment P= 0.376. However, TLC on the NAC group remained higher when compared with TLC on the placebo group.Conclusion: NAC administration significantly reduced levels of IL-10 and increased TLC; therefore, NAC has potential effects of increasing the effectiveness of antiretroviral therapy in HIV/AIDS patients, although it still needs to be studied further.J MEDICINE 2021; 22: 114-118